High‐dose treatment for malignant rhabdoid tumor of the kidney: No evidence for improved survival—The Gesellschaft für Pädiatrische Onkologie und Hämatologie (GPOH) experience. Issue 1 (26th August 2017) - Furtwängler, Rhoikos; Kager, Leo; Melchior, Patrick; Rübe, Christian; Ebinger, Martin; Nourkami‐Tutdibi, Nasenien; Niggli, Felix; Warmann, Steven; Hubertus, Jochen; Amman, Gabriele; Leuschner, Ivo; Vokuhl, Christian; et al.
Abstract: Background: Malignant rhabdoid tumor of the kidney (MRTK) is the most aggressive childhood renal tumor with overall survival (OS) rates ranging from 22% to 42%. Whether high‐dose chemotherapy with autologous stem‐cell transplantation (HDSCT) in an intensive first‐line treatment offers additional benefit is an ongoing discussion. Methods: A retrospective analysis of all 58 patients with MRTK from Austria, Switzerland, and Germany treated in the framework of consecutive, prospective renal/rhabdoid tumor studies SIOP9/GPO, SIOP93‐01/GPOH (where SIOP is International Society of Pediatric Oncology and GPOH is German Society of Pediatric Oncology and Hematology), SIOP2001/GPOH, and European Rhabdoid Tumor Registry from 1991 to 2014. Results: Median age at diagnosis was 11 months. Fifty percent of patients had metastases or multifocal disease at diagnosis (Stage IV). Local stage distribution was as follows: not done/I/II/III—1/6/11/40. Fifteen (26%) patients underwent upfront surgery. Thirty‐seven (64%) patients achieved a complete remission, 17 (29%) relapsed, 34 (59%) died of disease progression, and two (3%) died of treatment‐related complication. Mean time to the first event was 3.5 months. Two‐year EFS/OS (where EFS is event‐free survival) for the whole group was 37 ± 6%/38 ± 6%. Metastases/multifocal disease, younger age, and local stage III were associated with significantly inferior survival. Eleven (19%) patients underwent HDSCT (carboplatin + thiotepa, n = 6; carboplatin + etoposide + melphalan, n = 4; others, n = 1); 2‐year OS in this group was 60 ± 15% compared to 34 ± 8% in the non‐HDSCT group ( P = 0.064). However, the time needed from radiologic to histologic diagnosis, stem‐cell harvest, and HDSCT must also be taken into account to avoid selection bias by excluding the highest risk group with early progression (<90 days). Thus, 2‐year EFS only for patients without progression until day 90 was 60 ± 16% consolidated by HDSCT compared to 62 ± 11% without ( P = 0.8). Conclusion: Our retrospective analysis suggests comparable outcomes for patients with and without HDSCT, if adjusted for early disease progression.